Colorectal Metastasis From Lung Adenocarcinoma With Initial Gastrointestinal Symptoms: A Case Report and Literature Review - Yu Xin; Dan Liu; Dan Zang; Yan Sun; Jun Chen (Thoracic Cancer)
ABSTRACT Lung cancer (LC) is a malignant tumor with high morbidity and mortality. Nearly 50% of patients with primary LC have distant metastases at the time of initial diagnosis. LC usually metastasizes from the lungs to the liver, adrenal glands, brain, and bone, but rarely to the gastrointestinal (GI) tract. Most gastrointestinal metastases (GIM) from LC are found on the basis of primary LC. GIM of LC with GI symptoms as the initial symptom is extremely rare. Moreover, the overall survival time of lung cancer patients developing intestinal metastases is from 5 weeks to 1 year, and most patients will die within the first 6 months. This report describes an uncommon case of lung adenocarcinoma that metastasized to the colon with initial symptoms involving the GI tract. After immunotherapy, the condition was stable for more than 2 years, and he is currently in good condition.